2010
DOI: 10.1007/s11517-010-0606-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor cortical response during motion reflecting audiovisual stimulation: evidence from fractal EEG analysis

Abstract: Sensorimotor activity in response to motion reflecting audiovisual titillation is studied in this article. EEG recordings, and especially the Mu-rhythm over the sensorimotor cortex (C3, CZ, and C4 electrodes), were acquired and explored. An experiment was designed to provide auditory (Modest Mussorgsky's "Promenade" theme) and visual (synchronized human figure walking) stimuli to advanced music students (AMS) and non-musicians (NM) as a control subject group. EEG signals were analyzed using fractal dimension (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Our study showed that fast-tempo music excerpts induced a significant suppression in the alpha power over the right sensorimotor cortex, as compared to slow ones (Figure 3C). The alpha activity projected from the sensorimotor region was generally referred to as the mu rhythm, which has a well-established role in motor imagery [50] and engaged mirror neuron system during music listening [51]. The alpha suppression further reflects the engagement of sensory input or motor preparation/production [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that fast-tempo music excerpts induced a significant suppression in the alpha power over the right sensorimotor cortex, as compared to slow ones (Figure 3C). The alpha activity projected from the sensorimotor region was generally referred to as the mu rhythm, which has a well-established role in motor imagery [50] and engaged mirror neuron system during music listening [51]. The alpha suppression further reflects the engagement of sensory input or motor preparation/production [52].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding beta frequency band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), different studies reported correlation between this frequency range and cognitive functions, such as language and memory [4,26,42].…”
Section: Discussionmentioning
confidence: 99%
“…Sensorimotor rhythms are activated in central brain region [22,45]. Hence, EEG was recorded using 8 active electrodes (F3, F4, T7, C3, Cz, C4, T8, and Pz) placed in an elastic cap according to the international 10-20 system [25].…”
Section: Eeg Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators utilized Higuchi's, Katz's, and Petrosian's algorithms to calculate the FD. Each study enrolled 10 musicians and 10 non-musicians, and the studies concluded that FD can respond to changes in cortical activity (Hadjidimitriou et al, 2010(Hadjidimitriou et al, , 2011.…”
Section: Electroencephalogrammentioning
confidence: 99%